Effects of a non-pharmacological multicomponent intervention on delirium, sleep quality, and total sleep time among emergency intensive care unit patients in South Korea: a non-equivalent control group time-series study - Hye-Ji Kim; Mi-Kyoung Cho (Journal of Korean Biological Nursing Science, 2026)
Purpose: This study examined the effects of a non-pharmacological multicomponent intervention on delirium, sleep quality, and total sleep time in patients admitted to an emergency intensive care unit (EICU).Methods: A non-equivalent control group time-series design was used. Data were collected from the EICU of a tertiary hospital in South Korea between October 2025 and March 2026. A total of 48 patients were included, with 24 each in the experimental and control groups. The 2-day intervention comprised delirium prevention, sleep promotion, and intervention adherence management. Delirium was assessed using the Korean Nursing Delirium Screening Scale, sleep quality using the Korean version of the Richards-Campbell Sleep Questionnaire, and total sleep time was measured using a wearable device. Data were analyzed using generalized estimating equations, analysis of covariance (ANCOVA), and two-way repeated-measures ANCOVA using SPSS version 26.0 program.Results: Delirium scores were significantly lower in the experimental group than in the control group, with significant group (χ2 = 5.21, p = .022), time (χ2 = 12.86, p = .005), and group-by-time interaction effects (χ2 = 10.76, p = .013). Adjusted post-test sleep quality was significantly higher in the experimental group than in the control group (F = 16.15, p < .001, partial η2 = .26). Total sleep time showed significant main effects of group and time, whereas the group-by-time interaction was not significant (F = 2.61, p = .113, partial η2 = .05).Conclusion: The intervention helped prevent increases in delirium scores and improved sleep quality among EICU patients. This intervention may provide a feasible nursing strategy for critical care settings without the need for specialized equipment.